A review of clostridial diseases in rhinoceroses. Issue 3 (17th February 2023) - Angwenyi, Shaleen Kemunto Sarange; Hassell, James; Miller, Michele Ann; Mutinda, Mathew; Vitali, Francesca; Murray, Suzan
Abstract: Although rhinoceros conservation efforts are focused on anti‐poaching and combating wildlife trade, infectious diseases are an increasing threat to both free‐ranging and captive rhinoceros populations. Among these, clostridial infections with Clostridium perfringens, Paeniclostridium sordellii, and Clostridium novyi have caused acute disease in black and white rhinoceroses, characterized by a high mortality rate within very brief time spans. The acute nature, as well as limited knowledge of epidemiology, diagnosis, and management, make clostridial diseases an important threat to rhinoceros conservation. This article reviews historical cases of clostridial disease in rhinoceros with the aim of formulating a clearer understanding of the disease's epidemiology and using this information to make recommendations for its management in free‐ranging rhinoceroses. Acute colic and sudden death in rhinoceroses, together with necropsy findings of segmental hemorrhagic enteritis, should lead towards a tentative diagnosis of enteric clostridial disease, although detection and identification of specific toxins are required for a definitive diagnosis. Our findings indicate the need for further research into clostridial disease dynamics in wildlife species and provide the basis for this research in rhinoceroses.